1993
DOI: 10.1111/j.1540-4560.1993.tb00910.x
|View full text |Cite
|
Sign up to set email alerts
|

Attribution of Cognitive States to Animals: Anthropomorphism in Comparative Perspective

Abstract: Subjects were asked to indicate the likelihood that each of 30 animals (chosen as exemplars of the major phylogenetic classes) could engage in three complex cognitive tasks. Subjects were also asked to rate the extent to which they felt each animal was similar to themselves and whether they felt the animal experienced the world in a manner similar to the way they experienced it. The results showed that in all cases the perceived similarity and inferred cognitive abilities of animals proceeded from lesser to gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
136
1
3

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(150 citation statements)
references
References 24 publications
10
136
1
3
Order By: Relevance
“…Some participants made comments to justify their opinion, such as; "it is natural" and "in nature, it is normal". It has been suggested that there is a "hierarchy of concern" which is a function of the distance of relationship between the prey animal and primates (Eddy et al, 1993;Ings et al, 1997), and our results are consistent with this idea. The more closely a prey animal was related to primates, the fewer participants agreed that it should be fed alive to zoo animals or, if so, that it should be done off-exhibit.…”
Section: Discussionsupporting
confidence: 91%
“…Some participants made comments to justify their opinion, such as; "it is natural" and "in nature, it is normal". It has been suggested that there is a "hierarchy of concern" which is a function of the distance of relationship between the prey animal and primates (Eddy et al, 1993;Ings et al, 1997), and our results are consistent with this idea. The more closely a prey animal was related to primates, the fewer participants agreed that it should be fed alive to zoo animals or, if so, that it should be done off-exhibit.…”
Section: Discussionsupporting
confidence: 91%
“…With careful design, the task should be adaptable to any animal species. The test has particular value as a tool to assess emotion in taxa for which measures of emotion do not currently exist, are limited, are considered too difficult to study, or are simply ignored due to our anthropocentric approach to the study and attribution of animal emotions (Morris, Knight, & Lesley, 2012) and cognitive abilities (Eddy, Gallup, & Povinelli, 1993).…”
Section: Why Is Judgement Bias Important?mentioning
confidence: 99%
“…Given the human tendency to attribute mental states to some (but not all) animals (see Eddy et al 1993), this becomes a distinct possibility when applied to chimpanzees.…”
mentioning
confidence: 99%